INNOVATIVE COMPETENCY AS A CORE COMPETENCE OF FOREIGN LANGUAGE TEACHERS - Mannopova, Robiya (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The paper aims to analyse and review the existing previous research on the topic innovative competency of foreign language teachers, and uses narrative method as a research method. Based on the findings, the author defined the term innovative competency, and classified its components, levels, conditions analysing existing research papers.